Neuroprotective associations of apolipoproteins A-I and A-II with neurofilament levels in early multiple sclerosis - McComb, Mason; Krikheli, Maggie; Uher, Tomas; Browne, Richard W; Srpova, Barbora; Oechtering, Johanna; Maceski, Aleksandra Maleska; Tyblova, Michaela; Jakimovski, Dejan; Ramasamy, Deepa P; Bergsland, Niels; Krasensky, Jan; et al. (Journal of clinical lipidology, 2020)
BACKGROUND: The role of cholesterol homeostasis in neuroaxonal injury in multiple sclerosis is not known. OBJECTIVE: The objective of the study is to investigate the associations of cerebrospinal fluid (CSF) and serum neurofilament light chain levels (CSF-NfL and sNfL, respectively), which are biomarkers of neuroaxonal injury, with cholesterol biomarkers at the clinical onset of multiple sclerosis. METHODS: sNfL, serum cholesterol profile (total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol), serum apolipoprotein (Apo) levels (ApoA-I, ApoA-II, ApoB, and ApoE), and albumin quotient were obtained for 133 patients (63% female, age: 29.9 ± 8.0 years) during the first demyelinating event. CSF-NfL was available for 103 (77%) patients. RESULTS: CSF-NfL and sNfL were negatively associated with serum ApoA-II (P = .005, P < .001) and positively associated with albumin quotient (P < .001, P < .0001). In addition, higher CSF-NfL was associated with lower serum ApoA-I (P = .009) levels and higher sNfL was associated with lower high-density lipoprotein cholesterol (P = .010). In stepwise regression, age (P = .045), serum ApoA-II (P = .022), and albumin quotient (P < .001) were associated with CSF-NfL; albumin quotient (P = .002) and ApoA-II (P = .001) were associated with sNfL. Path analysis identified parallel pathways from ApoA-II (P = .009) and albumin quotient (P < .001) to the sNfL outcome that were mediated by CSF-NfL (P < .001). The associations of CSF-NfL with ApoA-I (P = .014) and ApoA-II (P = .015) and sNfL with ApoA-II (P < .001) remained significant after adjusting for number of contrast-enhancing lesions and T2 lesion volume. CONCLUSION: Lower serum ApoA-II and ApoA-I levels are associated with greater neuroaxonal injury as measured by CSF-NfL.
Keywords: Cerebrospinal fluid; Cholesterol; apolipoprotein A-II; neurofilamentové proteiny; Humans; Longitudinal Studies; Blood-brain barrier; Lipid; MRI; Apolipoprotein A-I; Multiple Sclerosis; neuroprotektivní látky; Neurofilament Proteins; Female; dospělí; Disease onset; Prospective Studies; Brain lesions; lidé; Neuroprotective Agents; Neurofilament light chain; Adult; Apolipoproteins; Multiple sclerosis; ženské pohlaví; longitudinální studie; roztroušená skleróza; Male; prognóza; Apolipoprotein A-II; mužské pohlaví; prospektivní studie; Prognosis; apolipoprotein A-I